SWOT Analysis in Determining Long-Term Competitive Strategies at PT. XYZ - Dilla Ghaisani Putri; Hapzi Ali (Siber Nusantara Review, 2025)
This study aims to formulate an effective long-term competitive strategy for PT. XYZ, a furniture company that manufactures sofas, mattresses, for domestic and export markets. The research object in this study is PT. XYZ, which is facing competitive challenges due to the increasing number of competitors and changing market preferences. The method used is qualitative descriptive with a case study approach, through the collection of data from literature studies. The analysis is carried out using SWOT tools to identify internal (strengths and weaknesses) and external (opportunities and threats) factors that affect the company's position. The results of the study show that PT. XYZ has strength in product quality and production capacity, but is weak in digitalization and global branding. Opportunities stem from the growth of e-commerce and design trends, while threats include fluctuations in raw material prices and fierce competition. The resulting strategy includes increasing production efficiency through digitalization, developing innovative products, expanding digital marketing, and strengthening internal management systems. This strategy is expected to be able to increase the competitiveness and market position of PT. XYZ on an ongoing basis.